Wiring The Writing Center - Hobson, Eric (University Press of Colorado, 1998)
Published in 1998, Wiring the Writing Center was one of the first few books to address the theory and application of electronics in the college writing center. Many of the contributors explore particular features of their own "wired" centers, discussing theoretical foundations, pragmatic choices, and practical strengths. Others review a range of centers for the approaches they represent. A strong annotated bibliography of signal work in the area is also included.